Gambaran Kualitas Hidup Pasien Rheumatoid Arthritis: Literature Review - Vidya Sulistiawati Dewi; Umi Yuniarni; Suwendar (Bandung Conference Series: Pharmacy, 2024)
Abstract. Rheumatoid arthritis (RA) is a common problem in Indonesia. The prevalence of RA sufferers in 2020 is not known with certainty, but it is estimated to reach no less than 1.3 million people, and as many as 335 million people in the world experience RA. The symptoms experienced by people with RA include joint stiffness, limited joint movement, swelling and pain, which interfere with daily activities and affect the patient's quality of life. In addition, RA can also affect psychological conditions such as depression and anxiety. This study was conducted using the systematic literature review (SLR) method. The quality of life of RA patients in Indonesia from eight articles concluded that patients with good quality of life were stated by five articles (57.5-100%), patients with moderate quality of life were stated by one article (53.33%) and patients with poor quality of life were stated by one article (90%). The quality of life of rheumatoid arthritis patients in foreign countries from five research articles namely research in Japan, Poland, Austria and Egypt concluded that patients with good quality of life were stated by two articles (45.5-100%), patients with fair quality of life were stated by one article (100%) and patients with poor quality of life were stated by two articles (38.5-100%). Factors that affect RA patients' quality of life include self-management, physical health, psychological, social and environmental relationships, compliance, knowledge and education, and age and gender. Abstrak. Rheumatoid arthritis (RA) menjadi salah satu masalah yang sering terjadi di Indonesia. Pada tahun 2020, prevalensi penderita RA belum diketahui pasti, namun diperkirakan mencapai tidak kurang dari 1,3 juta orang dan sebanyak 335 juta penduduk di dunia mengalami RA. Kondisi yang dialami pasien RA diantaranya kaku sendi, hambatan gerak persendian, bengkak, rasa sakit yang mengganggu aktivitas sehari-hari sehingga mempengaruhi kualitas hidup pasien. Selain itu, RA juga dapat mempengaruhi kondisi psikologis seperti depresi dan kecemasan. Penelitian ini dilakukan dengan metode Systematic Literature Review (SLR). Kualitas hidup pasien RA di Indonesia dari delapan artikel disimpulkan bahwa pasien dengan kualitas hidup baik dinyatakan oleh lima artikel (57,5-100%), pasien dengan kualitas hidup sedang dinyatakan oleh satu artikel (53,33%) dan pasien dengan kualitas hidup buruk dinyatakan oleh satu artikel (90%). Kualitas hidup pasien rheumatoid arthritis di negara luar dari lima artikel penelitian yaitu penelitian di Jepang, Polandia, Austria dan Mesir disimpulkan bahwa pasein dengan kualitas hidup baik dinyatakan oleh dua artikel (45,5-100%), pasien dengan kualitas hidup cukup dinyatakan oleh satu artikel (100%) dan pasien dengan kualitas hidup buruk dinyatakan oleh dua artikel (38,5-100%). Faktor-faktor yang mempengaruhi kualitas hidup pasien RA diantaranya self management, kesehatan fisik, psikologis, hubungan sosial dan lingkungan, tingkat kepatuhan, pengetahuan dan pendidikan, serta usia dan jenis kelamin.